The Development of Learning Design on Down Syndrome Children's Numbers Recognition - Leonard Leonard; Marisah Chaidir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This research aims to produce a mathematics instructional design emblem recognition numbers in grade 1 Elementary School Exceptional Tunagrahita, especially students with Down syndrome. This study design is based on the analysis of the mathematical competence requirements that should be owned by SDLB graduates first class as early competence to continue math in grade 2 and baseline characteristics of learners to fit the given instructional design. The collection of data by observation and interviews with teachers and parents of students. This research referring to the Instructional Development Model (MPI). This watchfulness consists of several steps, namely: (1) identify needs and writing instructional objectives, (2) the instructional analysis, (3) identify the behavior and character of early learners, (4) write aim instructional special, (5) composed result evaluation tool learns, (6) composed strategy instructional, (7) develop instructional materials, (8) carry out formative evaluation. The findings of the research that produced a design of a comprehensive learning in accordance with the purpose of learning mathematics learners tunagrahita particularly Down syndrome SDLB C grade 1.